TANGGUNG JAWAB PRODUK DALAM TRANSAKSI E-COMMERCE - Fitriah, Fitriah (Faculty of Law, University of Palembang, 2021)
Product responsibility in e-commerce transactions is the civil responsibility of business actors for losses suffered by consumers due to using the products they produce, the presumption of liability principle as a modification of the principle of responsibility on the reverse burden of proof. The principle of absolute responsibility adopted by producers gives very important attention to producers in protecting consumers as the weak party in carrying out a transaction, especially in e-commerce transactions. Product liability that adheres to stict liability can be very useful for consumers in protecting consumers in e-commerce transactions. So that consumers are not obliged to prove a mistake, it's just that consumers in a transaction should be able to prove that a product they use is defective so that it is detrimental to it.